The state of french in Lesotho: local “ownership” as the only viable way forward - Manyawu, Andrew T. (Institute of Southern African Studies, 2016)
It is common cause that French has a unique place in Sotho culture compared to its place in the cultures o f fellow SADC countries. But this language and culture, to which Lesotho owes, among other things, the Sesotho orthography, are slowly but surely vanishing from the landscape of modern Lesotho where French now seems to be the preserve of private or “ international" schools. This paper explores the need for indigenous Basotho, the vast majority of whom attend government-run schools, to study French. It goes further to propose possible changes to the national language policy and schools curriculum that will ensure that French is treated like any other subject in Lesotho's schools.